2017
DOI: 10.1111/jam.13427
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of growth conditions and DNA extraction techniques used in the molecular analysis of dermatophytes

Abstract: Most mycoses are caused by fungi that reside in nature. The severity of the infection depends on the pathogenic attributes, socioeconomic factors and local environmental conditions. Recent diagnosis increasingly relies on not only the clinical features. Molecular identifications have determined the need for a rapid and easy method of extracting DNA. Usually two factors have to be considered: maximize the DNA yield and ensure that the extracted DNA is susceptible to enzymatic reactions. These data suggest that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
2
9

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(56 citation statements)
references
References 47 publications
(123 reference statements)
0
45
2
9
Order By: Relevance
“…In the literature, there are no reports of the use of these techniques for dermatophyte identification in a wide range by many laboratories. In their investigations, Faggi et al, Brillowska‐Dąbrowska et al, Shehata et al , and Gnat et al show that this method can be a useful tool in molecular identification of tested isolates to the species level in full agreement with both culture‐based and ITS‐based methods. Our study also revealed that the PCR‐based band profiles obtained by MP‐PCR and PCR with primers (GTG) 5 and (GACA) 4 were reliable at the same level as ITS analyses, and were additionally easier to do.…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…In the literature, there are no reports of the use of these techniques for dermatophyte identification in a wide range by many laboratories. In their investigations, Faggi et al, Brillowska‐Dąbrowska et al, Shehata et al , and Gnat et al show that this method can be a useful tool in molecular identification of tested isolates to the species level in full agreement with both culture‐based and ITS‐based methods. Our study also revealed that the PCR‐based band profiles obtained by MP‐PCR and PCR with primers (GTG) 5 and (GACA) 4 were reliable at the same level as ITS analyses, and were additionally easier to do.…”
Section: Discussionmentioning
confidence: 93%
“…DNA was isolated from the dermatophytes with the phenol‐chloroform method as described by Gnat et al . Extraction controls were generated by subjecting distilled water to the same procedure.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations